A review of Indian species of Phrynocaria Timberlake (Coleoptera, Coccinellidae) with notes on synonymy and a new species from South India, hitherto misidentified as Coelophora circumusta (Mulsant) - Poorani, J.; Sankararaman, H.; Anusree, S. S. (Zootaxa, 2021)
Indian species of Phrynocaria Timberlake, 1943 (Coleoptera: Coccinellidae) are briefly reviewed and illustrated with notes on diagnosis, nomenclature, distribution and hosts. Coelophora circumusta (Mulsant, 1850), which has a limited distribution in India, is transferred to Phrynocaria (new combination) and Coelophora moseri Weise, 1902 is synonymized with it (new synonym). A new species, Phrynocaria perfida Poorani, sp. n. (Coleoptera, Coccinellidae) is described from South India based on specimens hitherto misidentified as a variety of C. circumusta. The validity of Phrynocaria funebris (Crotch, 1874) is confirmed based on examination and dissection of the type specimen; the species is redescribed and the male genitalia illustrated.